Evaluation of children with cystic fibrosis by impulse oscillometry when stable and at exacerbation - KARADAĞ, BÜLENT TANER; ERDEM ERALP, ELA; GÖKDEMİR, YASEMİN (WILEY, 2016)
BackgroundPulmonary function tests are important in the diagnosis and follow-up of airway disease in cystic fibrosis (CF). Conventional spirometry for which repeated forced expiration maneuver are needed is considered as the main method. Impulse oscillometry (IOS) is a non-invasive method, which needs minimal cooperation. We performed a prospective cross-sectional study to determine the pulmonary function in CF children with IOS, and evaluate the IOS measurements during acute exacerbation. We hypothesized that IOS can detect lung function impairment in CF patients and detect changes during acute exacerbations. MethodsCF patients aged 3-18 years were included as the study group and healthy children of the same age formed the control group. The patients were evaluated three times at 3-month intervals. Patients aged>6 years performed both spirometry and IOS while patients aged 6 years performed only IOS. In patients with acute exacerbation, spirometry and IOS were performed both at and after the exacerbation. ResultsForty-nine CF patients and 45 healthy children were enrolled to the study. Sixteen patients were admitted with acute exacerbation during the study. The resistance values (R5-10-15-20Hz) as well as Z5, Fres, and AX values of the patients were higher than those of the control group, while reactance values (X5-10-15-20Hz) were lower. R values as well as Z5, Fres, and AX values increased during exacerbation and decreased after treatment; X (10-15Hz) values decreased during exacerbation and increased after recovery (P<0.05). ConclusionsIOS may be useful to evaluate pulmonary functions and detect acute exacerbations in CF patients. Pediatr Pulmonol. 2016;51:1151-1158. (c) 2016 Wiley Periodicals, Inc.
Keywords: cystic fibrosis; pulmonary function testing; impulse oscillomety; spirometry; exacerbation; FORCED OSCILLATION TECHNIQUE; LUNG-FUNCTION; PRESCHOOL-CHILDREN; SPIROMETRY; RESPONSIVENESS; PARAMETERS